INTERCULTURAL TEACHING STRATEGIES IN THE DEPARTMENT OF LETTERS AND FOREIGN LANGUAGES OF THE UNIVERSITY OF TISSEMSILT - ALGERIA: REALITY FIELD AND PERSPECTIVES - Mohamed Fouzi IMESSAOUDENE; Cherif TOUADI (Universitaria Publishing House, Craiova, 2023)
This article, part of the Didactics of Languages-Cultures, focuses on the analysis of the strategies adopted by French language teachers working in the Department of Letters and Foreign Languages at the University of TISSEMSILT - Algeria, and this, in order to identify their perceptions regarding the use of the intercultural approach in the classroom. To this end, we will resort to a field survey through the realization of semi-structured interviews followed by an analysis of classroom practices.